Air ventilation assessment under unstable atmospheric stratification — A comparative study for Hong Kong. (15th February 2018) - Wang, Weiwen; Ng, Edward
Abstract: In most current air ventilation assessment (AVA) studies, a simple neutral assumption that does not consider thermal effects is adopted, particularly for numerical simulation practices. With statistics of daytime observations during summer in Hong Kong as an example, this study demonstrates that neutral atmospheric boundary conditions occur with a very low probability, which implies that current practices are indeed far away from reality. This study is devoted to addressing this knowledge gap by cross-comparisons of field measurements, wind tunnel tests, and large-eddy simulations (LES) under neutral and unstable conditions. It is found that LES-computed velocity ratios under unstable conditions are in line with field measurements, while results of simulations under neutral conditions are close to those of wind tunnel tests. Enhanced vertical mixing due to surface heating produces improved ventilation performance in the unstable case. The neutral assumption tends to underestimate pedestrian-level velocity ratios compared to a diabatic condition; hence it is deemed conservative when it is adopted in AVA practices. Moreover, stronger wind direction variance under unstable conditions results in weaker correlation between velocity ratios and frontal area indices than neutral conditions, which implies that street orientations become less important in ventilation under unstable conditions. Highlights: Diabatic conditions should be considered in urban ventilation studies. Enhanced mixing under unstable conditions produce larger velocity ratios. Ventilation assessment under a neutral assumption is conservative. Street orientation is less important for ventilation in unstable simulations.